Electrical pulse stimulation induces differential responses in insulin action in myotubes from severely obese individuals. (2nd December 2018) - Park, Sanghee; Turner, Kristen D.; Zheng, Donghai; Brault, Jeffrey J.; Zou, Kai; Chaves, Alec B.; Nielsen, Thomas S.; Tanner, Charles J.; Treebak, Jonas T.; Houmard, Joseph A.
Abstract : Key points: Exercise/exercise training can enhance insulin sensitivity through adaptations in skeletal muscle, the primary site of insulin‐mediated glucose disposal; however, in humans the range of improvement can vary substantially. The purpose of this study was to determine if obesity influences the magnitude of the exercise response in relation to improving insulin sensitivity in human skeletal muscle. Electrical pulse stimulation (EPS; 24 h) of primary human skeletal muscle myotubes improved insulin action in tissue from both lean and severely obese individuals, but responses to EPS were blunted with obesity. EPS improved insulin signal transduction in myotubes from lean but not severely obese subjects and increased AMP accumulation and AMPK Thr 172 phosphorylation, but to a lesser degree in myotubes from the severely obese. These data reveal that myotubes of severely obese individuals enhance insulin action and stimulate exercise‐responsive molecules with contraction, but in a manner and magnitude that differs from lean subjects. Abstract: Exercise/muscle contraction can enhance whole‐body insulin sensitivity; however, in humans the range of improvements can vary substantially. In order, to determine if obesity influences the magnitude of the exercise response, this study compared the effects of electrical pulse stimulation (EPS)‐induced contractile activity upon primary myotubes derived from lean and severely obese (BMI ≥ 40 kg/m 2 ) women. Prior to muscle contraction, insulin action was compromised in myotubes from the severely obese as was evident from reduced insulin‐stimulated glycogen synthesis, glucose oxidation, glucose uptake, insulin signal transduction (IRS1, Akt, TBC1D4), and insulin‐stimulated GLUT4 translocation. EPS (24 h) increased AMP, IMP, AMPK Thr 172 phosphorylation, PGC1α content, and insulin action in myotubes of both the lean and severely obese subjects. However, despite normalizing indices of insulin action to levels seen in the lean control (non‐EPS) condition, responses to EPS were blunted with obesity. EPS improved insulin signal transduction in myotubes from lean but not severely obese subjects and EPS increased AMP accumulation and AMPK Thr 172 phosphorylation, but to a lesser degree in myotubes from the severely obese. These data reveal that myotubes of severely obese individuals enhance insulin action and stimulate exercise‐responsive molecules with contraction, but in a manner and magnitude that differs from lean subjects. Key points: Exercise/exercise training can enhance insulin sensitivity through adaptations in skeletal muscle, the primary site of insulin‐mediated glucose disposal; however, in humans the range of improvement can vary substantially. The purpose of this study was to determine if obesity influences the magnitude of the exercise response in relation to improving insulin sensitivity in human skeletal muscle. Electrical pulse stimulation (EPS; 24 h) of primary human skeletal muscle myotubes improved insulin action in tissue from both lean and severely obese individuals, but responses to EPS were blunted with obesity. EPS improved insulin signal transduction in myotubes from lean but not severely obese subjects and increased AMP accumulation and AMPK Thr 172 phosphorylation, but to a lesser degree in myotubes from the severely obese. These data reveal that myotubes of severely obese individuals enhance insulin action and stimulate exercise‐responsive molecules with contraction, but in a manner and magnitude that differs from lean subjects.